Transforming the Lives of Breast Cancer Patients: A Qualitative Study - Zakariyati; Ariyanti Saleh; Rina Masadah; Erfina (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The transformation of the lives of breast cancer patients is an important issue as the incidence of this disease increases. Breast cancer is the most common type of cancer among women, often causing emotional challenges, including anxiety and depression, as well as identity changes. This study aims to explore the experiences of breast cancer patients undergoing chemotherapy, with a focus on the physical, psychological, social, and spiritual impacts. Methods: This study was qualitative research, and information was collected by conducting in-depth interviews with 11 patients, 5 nurses, 2 survivors, and 1 doctor at Tk.II Pelamonia Hospital, Indonesia. Results:4 essential points were found, namely changes in daily life, including physical and psychological impact, social support from family and friends, spirituality, and hope and motivation. Conclusion: There is a need for a holistic care approach that integrates social and spiritual support to improve the quality of life of breast cancer patients during treatment.